Hepatitis B vaccine among healthcare workers: factors associated with the dimensions of the Health Belief Model - Yvanilson Costas Farias Junior; Fernanda de Oliveira Souza; Deisy Vital dos Santos; Margarete Costa Heliotério; Paloma de Sousa Pinho; Tânia Maria de Araújo (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To investigate the association between the dimensions of the Health Belief Model (HBM) and complete vaccination for hepatitis B among healthcare workers (HCW). Methods: Cross-sectional epidemiological study with HCW in Primary Health and Medium Complexity Care. Univariate and bivariate analyses were performed to test the association between the outcome variable (complete vaccination for hepatitis B based on self-report) and the variables of the HBM dimensions. Prevalence ratio (PR) and its respective 95% confidence intervals (95%CI) were calculated. Results: 453 HCW participated. The prevalence of complete vaccination for hepatitis B was 56.9%. In the final analysis model, the following variables were associated with complete vaccination for hepatitis B: chances of having hepatitis B (PR=1.73) - related to the susceptibility dimension; disease severity (PR=0.74) - related to severity; reduced risk of absenteeism (PR=1.29) - related to benefits; not spending time to get vaccinated (PR=1.41) and not worrying about Events Supposedly Attributable to Vaccination or Immunization (PR=1.43) - related to barriers. Conclusions: The completeness of the hepatitis B vaccination schedule, reported by the investigated HCW, reveals the prevalence is below the target established by the Ministry of Health, which follows the national scenario of low coverage presented for other age groups. Understanding the risk perception and severity of hepatitis B can contribute to increasing the prevalence of vaccination for this infection.